The Oral Health Impact Profile-14:: a unidimensional scale? - Camila Mello dos Santos; Branca Heloisa de Oliveira; Paulo Nadanovsky; Juliana Balbinot Hilgert; Roger Keller Celeste; Fernando Neves Hugo
The aim of this study was to investigate the dimensional structure of the Oral Health Impact Profile-14: (OHIP-14). Data was obtained from studies carried out in Rio de Janeiro (N = 504) and Carlos Barbosa (N = 872), in the State of Rio Grande do Sul, Brazil. Exploratory factor analysis (EFA) was performed to identify the latent dimensions of the OHIP-14. Confirmatory factor analysis (CFA) was carried out of both samples to compare the one-dimensional structure found by the EFA and the proposed three-dimensional structure. This factorial structure was assessed using goodness-of-fit indices. In the Rio de Janeiro study, the eigenvalue was 9.2 and this one factor explained 65.6% of total variance, while in the Carlos Barbosa study the eigenvalue was 7.9 and this one factor explained 56.6% of variance. CFA indicated an adequate fit of the one-factor model for the Rio de Janeiro study (RMSEA = 0.04; CFI = 0.98; TLI = 0.98) and for the Carlos Barbosa study (RMSEA = 0.05; CFI = 0.97; TLI = 0.97). Our findings suggest that the OHIP-14 measures one single construct.